1993
DOI: 10.1111/j.1365-2958.1993.tb01112.x
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide sequence of the first cosmid from the Mycobacterium leprae genome project: structure and function of the Rif‐Str regions

Abstract: The nucleotide sequence of cosmid B1790, carrying the Rif-Str regions of the Mycobacterium leprae chromosome, has been determined. Twelve open reading frames were identified in the 36716bp sequence, representing 40% of the coding capacity. Five ribosomal proteins, two elongation factors and the beta and beta' subunits of RNA polymerase have been characterized and two novel genes were found. One of these encodes a member of the so-called ABC family of ATP-binding proteins while the other appears to encode an en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0

Year Published

1994
1994
2005
2005

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(50 citation statements)
references
References 34 publications
(13 reference statements)
2
48
0
Order By: Relevance
“…The L3 fragment of M. bovis BCG used for screening the library was generated with primers 31 and 32, which are derived from the Mycobacterium leprae sequence (Honoré et al, 1993). With these primers, a homologous DNA fragment was generated under low-stringency conditions (40ЊC) using M. bovis BCG DNA as template.…”
Section: Dna Techniquesmentioning
confidence: 99%
“…The L3 fragment of M. bovis BCG used for screening the library was generated with primers 31 and 32, which are derived from the Mycobacterium leprae sequence (Honoré et al, 1993). With these primers, a homologous DNA fragment was generated under low-stringency conditions (40ЊC) using M. bovis BCG DNA as template.…”
Section: Dna Techniquesmentioning
confidence: 99%
“…The multi-national architecture of the B. subtilis sequencing consortium has dictated the latter approach, with individual groups being responsible for developing their own sequencing strategy. Whilst cosmid libraries have been used to create overlapping libraries of individual Saccharomyces cerevisiae [23] and Caenorhabditis elegans [24] chromosomes and for the genome of Mycobacterium leprae [25], and lambda libraries for the E. coli genome [26], it has proved impossible to construct cosmid or lambda libraries that completely cover the B. subtilis chromosome. This is because large fragments of B. subtilis DNA have been found to be unstable in E. coli due to their high AT content (43% GC) and the elevated levels of expression of many B. subtilis genes in this host [27,28].…”
Section: Sequencing Strategiesmentioning
confidence: 99%
“…Ascribing important functions or contacts to regions 4b and 4c is made highly questionable by the finding that nearly all of these sequences are deleted in M. leprae 13' (Honore et al 1993). However, five different insertions and one substitution in or near the corresponding region of the yeast Pol II largest subunit confer sensitivity to 6-azauracil and can be suppressed by overproduction of the THIS elongation factor (Fig.…”
Section: Interval 4--coincidence Of Some Substitutions With a Site Ofmentioning
confidence: 99%
“…In 13, they are a large deletion found in several chloroplast RNA polymerases (Hudson et al 1988), a sequence resembling one found in the RNase barnase (Shirai and Go 1991), sites of substitutions leading to streptolydigin (Heisler et al 1993;Severinov et al 1993) or rifampicin (Lisitsyn et al 1984;Severinov et al 1993} resistance, location where f3 is divided in Chlamydomonas chloroplasts (Fong and Surzycki 1992), the major site of trypsin cleavage in E. coli RNA polymerase (Borukhov et al 1991), a deletable hinge region in ~ (Glass et al 1986), and sites where primer substrate analogs cross-link to the [3 subunit (Grachev et al 1989). Features noted in ~' are a putative Cys4-Zn 2+ motif conserved in most ~' homologs (Borukhov et al 1991), a sequence similarity to DNA polymerase I (Allison et al 1985), a site where ~' homologs are split in cyanobacteria and chloroplasts (Hudson et al 1988;Xie et al 1989;Igloi et al 1990;Shimada et al 1990;Fong and Surzycki 1992), a region in which Ama-resistance substitutions occur in Pol II ~' subunit homologs (Bartolomei and Corden 1987;Chen et al 1993), a site where the 3' end of the nascent transcript cross-links to ~' (Borukhov et al 1991), a site where an insertion occurs in the rice chloroplast ~' subunit (Shimada et al 1990), and a site where a large deletion occurs in M. leprae fY (Honore et al 1993). …”
Section: All But One Termination-altering Substitution Occurred In Fomentioning
confidence: 99%